MYTHOLOGIES OF AN ARTIST OF THE THEATRE. KAZIMIERZ DEJ MEK AND JERZY GROTOWSKI - Sobiecka, Anna (Porównania, 2019)
The contemporary Polish prose has once more become inspired by the novel concerning an artist, and attempts to mythologise the artist’s image of the world of the theater. In this article, I shall cover a range of texts which show a peculiar interest in the great figures of the Polish theatre – Kazimierz Dejmek and Jerzy Grotowski. The chosen works adopt the archetypes of both the characters, as well as of the plot, from the overlapping areas of the two artists’ personal and professional scenic lives, conveying the artists’ real-world experiences into fiction. The key strategy used in the mentioned works occurs in two basic varieties – the pamphlet novel and the parabolic novel. The mythologisation of the artist is dependent on the creation of phantasmatic biographies, based on a unique type of an unspoken agreement between the author and the reader.